The factors influencing the acceptance of Islamic Banking among muslim consumers in Shah Alam / Nur Anisah Omar and Nurul Syuhada Abd Aziz - Omar, Nur Anisah; Abd Aziz, Nurul Syuhada (2022)
Intense competition between Islamic Banking and Conventional Banking makes it difficult for customers to choose between the two, especially for people who are not financially literate. Most Muslim customers choose Islamic Banking due to religious obligations, but this research aims to study beyond that factor for the customers’ acceptance. This is due to the low acceptance of Islamic Banking among Muslim customers. The stakeholders, including customers, legislators, and even the employees of Islamic Banking Institutions, especially those with low awareness and knowledge, would typically view and assume that Islamic Banking’s products are similar to Conventional Banking’s. According to Bank Negara Malaysia (2019), approximately 60% of Malaysia's small and medium businesses are unfamiliar with the availability of Islamic finance options which can be concluded that among that 60% there are Muslims who are unaware and do not accept the Islamic Banking products and services. This research studies the factors of knowledge, service quality and relative advantage and trustworthiness that can influence the acceptance of Islamic Banking for 390 Muslim respondents in Shah Alam. The study revealed that all the independent variables have a significant relationship with the dependent variable and trustworthiness is the key factor that influences the acceptance of Islamic banking among all those four factors. Therefore, hopefully this research would be able to be useful in increasing customers’ awareness or for the parties concerned in the efforts to increase the customers’ acceptance.